Parity and the Incidence of Chronic Energy Deficiency (CED) in Pregnant Women: A Case-Control Study - Nagia, Rosi Putri; Rositagaol, Uli; Revinovita, Revinovita; Bakri, Deffi Uprianti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Chronic Energy Deficiency (CED) remains a significant nutritional challenge among pregnant women in developing countries, including Indonesia. CED is defined as a mid-upper arm circumference (MUAC) below 23.5 cm and poses serious risks to maternal and neonatal health outcomes. Parity, defined as the number of live births a woman has had, has been theoretically linked to nutritional depletion and an increased risk of CED. However, evidence on this relationship is inconsistent across different populations and settings. This study aimed to determine the relationship between parity and the incidence of CED in pregnant women at the Pasar Atas Village Midwife Practice, Bangko, Jambi, Indonesia. Methods: A case-control study with a 1:1 ratio was conducted using secondary data from the antenatal care register of Pasar Atas Village Midwife Practice for 2023–2024. A total of 90 pregnant women were enrolled: 45 cases (CED, MUAC <23.5 cm) and 45 matched controls (non-CED, MUAC ≥23.5 cm). Controls were matched to cases by maternal age. Parity was categorized as at-risk (≥3 deliveries) and not-at-risk (<3 deliveries). Data were analyzed using univariate and bivariate (chi-square) analyses with SPSS. Statistical significance was set at p<0.05. Results: Of all 90 respondents, 50% experienced CED. The majority of respondents had non-risk parity (96.7%, n=87). Among the at-risk parity group (n=3), all were in the non-CED group. Chi-square analysis showed no statistically significant association between parity and CED incidence (p-value=0.240). Conclusion: Parity was not significantly associated with CED among pregnant women in this study. The predominance of non-risk parity in the population may have limited the statistical power to detect an association. Other determinants such as pre-pregnancy weight, dietary intake, and inter-pregnancy interval may play more important roles in CED risk and should be further investigated.